Photophysiological responses of bottom sea-ice algae to fjord dynamics and rapid freshening - Forgereau, Zoé L.; Lange, Benjamin A.; Gradinger, Rolf; Assmy, Philipp; Osanen, Janina E.; García, Laura M.; Søreide, Janne E.; Granskog, Mats A.; Leu, Eva; Campbell, Karley (Frontiers in Marine Science, 2023)
Sea ice algae have a broad salinity tolerance but can experience stress during rapid decreases in salinity that occur with seasonal ice melt and during ice sample melt. This study investigated the impact of salinity on the photophysiological responses of bottom-ice algal communities from two Svalbard fjords (Tempelfjorden and Van Mijenfjorden). To further investigate the impact of salinity alone, and particularly to rapid freshening, the responses of a lab-cultured ice algal community from Van Mijenfjorden were assessed. Photophysiological responses were mainly determined via 14C-based incubations which provided photosynthesis-irradiance curves. Main findings showed that i) the bottom-ice algal community in Tempelfjorden was characterized by lower photosynthetic efficiency and chlorophyll a biomass than the Van Mijenfjorden communities, and ii) a lab-cultured ice algal community from Van Mijenfjorden dominated by pennate diatoms had significantly lower photosynthetic efficiency, maximum photosynthesis and photoacclimation index after a decrease in salinity from 33 to 10. The lower photosynthetic efficiency and chlorophyll a biomass at Tempelfjorden may be attributed to the almost two-fold lower bulk-ice salinity in Tempelfjorden compared to Van Mijenfjorden, which was likely associated with freshwater inputs from the tidewater glacier Tunabreen during sea ice formation. Other factors such as under-ice light intensities, brine volume fraction and brine nutrient concentrations likely also contributed to variability in ice algal response. Furthermore, experimental results indicated that the cultured Van Mijenfjorden community was negatively impacted by a rapid (within 4 to 24 h) reduction in salinity from 33 to 10. We further documented a significant start of recovery of these algae after 168 h. From this work, we surmise that decreases in surface water salinity, for example arising from the intensifying freshening of fjord waters, may only cause temporary changes in ice algal photoacclimation state and thus in chlorophyll a biomass. Further, this study also supports the need for salinity buffered melt of sea ice samples to reduce artificial bias in biological measurements.